The completed macronuclear genome of a model ciliate Tetrahymena thermophila and its application in genome scrambling and copy number analyses - Sheng, Yalan (Sci China Life Sci, 2020)
The ciliate Tetrahymena thermophila has been a powerful model system for molecular and cellular biology. However, some investigations have been limited due to the incomplete closure and sequencing of the macronuclear genome assembly, which for many years has been stalled at 1,158 scaffolds, with large sections of unknown sequences (available in Tetrahymena Genome Database, TGD, http://ciliate.org/). Here we completed the first chromosome-level Tetrahymena macronuclear genome assembly, with approximately 300× long Single Molecule, Real-Time reads of the wild-type SB210 cells—the reference strain for the initial macronuclear genome sequencing project. All 181 chromosomes were capped with two telomeres and gaps were entirely closed. The completed genome shows significant improvements over the current assembly (TGD 2014) in both chromosome structure and sequence integrity. The majority of previously identified gene models shown in TGD were retained, with the addition of 36 new genes and 883 genes with modified gene models. The new genome and annotation were incorporated into TGD. This new genome allows for pursuit in some underexplored areas that were far more challenging previously; two of them, genome scrambling and chromosomal copy number, were investigated in this study. We expect that the completed macronuclear genome will facilitate many studies in Tetrahymena biology, as well as multiple lines of research in other eukaryotes.